Optical-Helicity-Dependent Orbital and Spin Dynamics in Two-Dimensional Ferromagnets - Li, Shuo; Wang, Ran; Frauenheim, Thomas; He, Junjie (The journal of physical chemistry letters, 2024)
Disentangling orbital (OAM) and spin (SAM) angular momenta in the ultrafast spin dynamics of two-dimensional (2D) ferromagnets on subfemtoseconds is a challenge in the field of ultrafast magnetism. Herein, we employed a non-collinear spin version of real-time time-dependent density functional theory to investigate the orbital and spin dynamics of the 2D ferromagnets Fe3GeTe2 (FGT) induced by circularly polarized light. Our results show that the demagnetization of the Fe sublattice in FGT is accompanied by helicity-dependent precession of the OAM and SAM excited by circularly polarized lasers. We further identify that precession of the OAM and SAM in FGT is faster than demagnetization within a few femtoseconds. Remarkably, circularly polarized lasers can significantly induce a periodic transverse linear response of the OAM and SAM on very ultrafast time scales of ∼600 attoseconds. Our finding suggests a powerful new route for attosecond regimes of the angular momentum manipulation to coherently control helicity-dependent orbital and spin dynamics in 2D ferromagnets.